2017
DOI: 10.1175/jcli-d-17-0225.1
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Model Structural Uncertainty in Climate Model Projections—A Rank-Based Model Combination Approach

Abstract: Future changes in monthly precipitation are typically evaluated by estimating the shift in the long-term mean/variability or based on the change in the marginal distribution. General circulation model (GCM) precipitation projections deviate across various models and emission scenarios and hence provide no consensus on the expected future change. The current study proposes a rank/percentile-based multimodel combination approach to account for the fact that alternate model projections do not share a common time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…GCMs that are capable of reproducing relevant weather patterns for the impact sector of interest. In addition, the development of the most likely probabilistic climate projection by weighting the performance of various GCMs in long-term hindcast simulations may be a promising solution(Das Bhowmik, Sharma, & Sankarasubramanian, 2017). The crop model parameters were perturbed based on the calibrated set of crop model parameters and their possible ranges.…”
mentioning
confidence: 99%
“…GCMs that are capable of reproducing relevant weather patterns for the impact sector of interest. In addition, the development of the most likely probabilistic climate projection by weighting the performance of various GCMs in long-term hindcast simulations may be a promising solution(Das Bhowmik, Sharma, & Sankarasubramanian, 2017). The crop model parameters were perturbed based on the calibrated set of crop model parameters and their possible ranges.…”
mentioning
confidence: 99%
“…Note that, GCM 20th century run and future projections under different RCPs exhibit a temporal mismatch with the observed records and with each other. The model uncertainty in projected streamflow can be reduced by adopting a performance-based multimodel combination approach or simply by applying equal weight to ensemble members [36]. Table 1).…”
Section: Estimation Of Future Changesmentioning
confidence: 99%
“…Although, multiple climate models was suggested over a single model, Knutti (2008) reported that major simulation errors might arise in multiple GCMs either from model parameterization or from the inadequate understanding of physical processes. Therefore, multiple GCMs or multiple members within a GCM ensemble show significant differences in their monthly outputs (Johnson et al ., 2011; Das Bhowmik et al ., 2017). Future projections of GCMs exhibit different magnitudes of change in the global mean surface air temperature, as compared to the 20th century records (Stocker et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most optimal model combination techniques have focused primarily on weather and climate forecasts, mostly ignoring the prospect of performance‐based model combination in reducing uncertainty in climate change projections. A recent study showed multi‐model combination based on asynchronous measurement can perform better than equal weighting approach in estimating future projections of precipitation (Das Bhowmik et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation